Longitudinal variations of positive dayside ionospheric storms related to recurrent geomagnetic storms - Dmitriev, A. V. (2013)
We have performed an analysis of case events and statistics of positive ionospheric storms in the dayside region of the equatorial ionization anomaly during recurrent geomagnetic storms (RGSs), which dominate in geomagnetic and ionospheric conditions on the declining phase of solar activity in 2004 to 2008. It is shown that total electron content (TEC) has a tendency to minimize before the beginning of RGSs and to peak 3 to 4 days after, i.e., on the RGS recovery phase produced by high‐intensity long‐duration continuous auroral activity. The maximum of TEC coincides with the maximum of solar wind velocity within high‐speed solar wind streams. An analysis of electron content vertical profiles, derived from two independent methods using ionosondes and Constellation Observing System for Meteorology, Ionosphere, and Climate /Formosa Satellite mission‐3 radio occultation, showed that in the maximum of an ionospheric storm on 28 March 2008, the F2 layer thickens, NmF2 increases by ~50%, and hmF2 elevates by a few tens of kilometers. The response of positive ionospheric storms to solar, heliospheric, and geomagnetic drivers reveals a prominent longitudinal asymmetry. In the longitudinal range from −90° to 90°, the solar illumination plays a major role, and in the range from 90° to −120°, the influence of heliospheric and geomagnetic drivers becomes significant. The highest correlations of the TEC enhancements with the heliospheric and geomagnetic drivers were found during December–February (r increased from ~0.3 to ~0.5). We speculate that the dynamics controlling this might result from an effect of solar zenith angle, storm time effects of thermospheric ΣO/N2 enhancement, and penetrating electric fields of interplanetary and magnetospheric origin.